Humic Substances (IntechOpen, 2021)
Present in soil and water, humic substances are the most widespread organic compounds, naturally occurring from a physical, chemical, and microbiological transformation of biomolecules. They represent about 25% of the total organic carbon on the Earth and comprise up to 75% of the dissolved organic carbon in water, making them important for multiple environmental processes in both soil and aquatic systems. Despite many decades of extensive study, the formation mechanisms of humic substances are still a subject of discussion and controversy. This book examines the dynamics of humic substances, their physicochemical and biological properties, and methods for their extraction and characterization. The book also sheds light on recent advances and applications of humic substances in agriculture, environment, industry, and medicine.